The Influence of Financial Literacy on Consumptive Behavior Among High School Students in Jakarta - Mosca Shabrina Djajadiningrat (Integrasi Sains Media, 2023)
This research addresses the prevalent issue of consumerism and its relationship with financial literacy among high school students in Jakarta. Influenced by rapid urbanization, global cultural norms, and digital technologies, consumptive behavior is prominent, especially among urban youth. Recognizing financial literacy, which encompasses financial knowledge, attitudes, and behaviors, as a critical factor influencing consumerism, this study sought to examine this complex interplay. This study was collected through an online questionnaire and involved 120 respondents of high school students in Jakarta. The multiple linear regression analysis was performed using SPSS to analyze the results. The result revealed a moderate level of financial literacy among high school students in Jakarta, with a score of 63.55. However, this score is very close to the lower end of the moderate spectrum, indicating a widespread low level of financial literacy. At the same time, the high cost of living in Jakarta and the ready availability of consumer goods can lead to uninformed financial decisions and impulsive spending. The findings underscore the significant impact of financial literacy, which includes financial knowledge, behavior, and attitudes, on the consumptive behavior of these students. Therefore, fostering improved student financial attitudes and behaviors is essential for prudent financial management and spending. Given the scope of the study, future research could include additional variables that impact consumer behavior to provide a more comprehensive understanding.